ระบบงบประมาณแบบมุ่งเน้นผลงาน: กรณีศึกษา นโยบายการแก้ไขปัญหาความยากจนในประเทศไทย (THE PERFORMANCE-BASED BUDGETING SYSTEM: A STUDY OF POVERTY REDUCTION POLICY IMPLEMENTATION IN THAILAND) - ตระการวนิช, พุทธิมา; บุราคม, พลพัทร; ตรีรัตน์, นวลน้อย; เจริญงาม, โชติชัย (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2011)
รายงานการวิจัยฉบับนี้มีวัตถุประสงค์หลักเพื่อระบุปัจจัยที่มีผลต่อความสำเร็จในการจัดทำและบริหารงบประมาณที่เกี่ยวข้องกับการนำนโยบายการแก้ไขปัญหาความยากจนในระดับจังหวัดภายใต้ระบบงบประมาณแบบมุ่งเน้นผลงานไปปฏิบัติในประเทศไทย จากการวิจัยพบว่า ความสำเร็จดังกล่าวมีผลมาจากการที่จังหวัดได้รับข้อมูลที่เพียงพอ และได้รับการสนับสนุนที่เหมาะสมจากสำนักงบประมาณและหน่วยงานกลางอื่นๆ ในทางตรงกันข้ามความชัดเจนของนโยบายฯ มีผลทำให้ระดับความสำเร็จในการจัดทำและบริหารงบประมาณฯ ลดลง อีกทั้งความสามารถของจังหวัดในการนำระบบงบประมาณแบบมุ่งเน้นผลงานมาใช้มีผลทำให้ระดับความสำเร็จดังกล่าวลดลงด้วย จากการศึกษาในครั้งนี้ผู้วิจัยได้นำเสนอข้อเสนอแนะต่อรัฐบาล ผู้บริหารและเจ้าหน้าที่ผู้ปฏิบัติงานในจังหวัด และสำนักงบประมาณเกี่ยวกับการพัฒนาสู่ความสำเร็จในการจัดทำและบริหารงบประมาณที่เกี่ยวข้องกับการนำนโยบายการแก้ไขปัญหาความยากจนภายใต้ระบบงบประมาณแบบมุ่งเน้นผลงานไปปฏิบัติในหลายประเด็น ได้แก่ การมีข้อมูลและระบบการบริหารจัดการข้อมูลที่ครบถ้วน การพัฒนาแผนบูรณาการสำหรับยุทธศาสตร์การแก้ไขปัญหาความยากจน การมุ่งเน้นความโปร่งใสและความรับผิดชอบในการปฏิบัติงานของจังหวัด การส่งเสริมบทบาทหน้าที่และความรับผิดชอบของสำนักงบประมาณ เป็นต้น คำสำคัญ: ระบบงบประมาณแบบมุ่งเน้นผลงาน รายจ่ายสาธารณะ การนำนโยบายไปปฏิบัติ This research was conducted mainly in order to identify the primary determinants of the success of budget preparation and execution of the Performance-Based Budgeting System (PBBS) related to poverty reduction program implementation at the provincial level in Thailand. The results from the empirical analysis indicated that provinces are more likely to have successful budget preparation and execution of the PBBS related to poverty reduction program implementation when they have sufficient information and appropriate facilitations provided by the Bureau of the Budget and other central agencies. However, precise poverty reduction policy could cause a lower level of success with budget preparation and execution of the PBBS related to poverty reduction program implementation. Finally, the high capacity of a province in adopting the PBBS could lead to low level of successful budget preparation and execution of the PBBS related to poverty reduction program implementation. In order to have successful budget preparation and execution in the PBBS related to poverty reduction program implementation, the recommendations have been placed into three groups, which are policy makers/government, provincial executives and officials, and the Bureau of the Budget. They include, for instance, the provision of comprehensive information and information management system, the development of integration plan for poverty reduction strategies, the existence of the accountability and transparency in the provinces, and the promotion of roles and responsibilities of the Bureau of the Budget. Keywords: Performance-Based Budgeting System, Public Expenditures, Policy Implementation